PERBANDINGAN GAYA HIDUP ETNIS CINA - Ngurah Wisnu Wijayaputra; C Handoyo Wibisono (Modus, 2013)
This study aims to determine the lifestyle of ethnic Chinese and ethnic Bali in Yogyakarta and the diference in his lifestyle. The research was conducted by taking a sample of Chinese and Balinese masyarakatetnis in Yogyakarta and aged between 20 to 49 years. The results of this study showed no diference between ethnic Balinese lifestyle with ethnic Chinese. The results of this study also showed a diference in price awareness and confdence between ethnic Balinese ethnic Chinese.Keywords : lifestyle of ethnic, consumer behavior